2018
DOI: 10.1177/1071100718754421
|View full text |Cite
|
Sign up to set email alerts
|

Intratissue Percutaneous Electrolysis vs Corticosteroid Infiltration for the Treatment of Plantar Fasciosis

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 39 publications
3
25
0
6
Order By: Relevance
“…Comparison with other studies cannot be performed as Valera-Garrido et al did not measure function or range of motion; however, using ultrasound, they determined the reduction of degenerative structural changes observed in LE. Studies applying PE to other musculoskeletal pain conditions such as subacromial pain syndrome [31], plantar fasciosis [32], and patellar tendinopathy [14] showed significant improvements in function, which agree with those observed in this study. In terms of other secondary outcomes measured in this study, it must be noted that no improvements were observed in quality of life.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparison with other studies cannot be performed as Valera-Garrido et al did not measure function or range of motion; however, using ultrasound, they determined the reduction of degenerative structural changes observed in LE. Studies applying PE to other musculoskeletal pain conditions such as subacromial pain syndrome [31], plantar fasciosis [32], and patellar tendinopathy [14] showed significant improvements in function, which agree with those observed in this study. In terms of other secondary outcomes measured in this study, it must be noted that no improvements were observed in quality of life.…”
Section: Discussionsupporting
confidence: 91%
“…Follow-up measures at one and three months demonstrate that effects remained in time, as Valera-Garrido et al observed in their study [6]. Data yielded by this study also agreed with those regarding pain improvement obtained in other studies that used PE in other musculoskeletal disorders, such as subacromial pain syndrome [31], plantar fasciosis [32], and patellar tendinopathy [14]. Due to the previous results, percutaneous electrolysis could be considered an appropriate approach for diverse musculoskeletal pain syndromes.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, controlled tendon loads with exercise will be clearly needed to be combined with percutaneous electrolysis to facilitate the process of collagen tissue proliferation, thus improving the biomechanical properties of the tendon. This hypothesis is partially supported by randomized clinical trials showing that combining percutaneous electrolysis with a progressive exercise program represents a promising management strategy for tendinopathies of the elbow [ 19 ], shoulder [ 21 ], or knee [ 17 ]. Future trials determining the biological effects of combing percutaneous electrolysis with active therapies such as exercise would help to elucidate the underlying mechanisms of the clinical benefits of this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, current results should be considered in the investigated scenario. Finally, the application of percutaneous electrolysis is usually ultrasound-guided [ 16 , 17 , 18 , 19 , 20 , 21 ]. In the current study, the technique was not ultrasound-guided, which could have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…9 The needle is directed at the soft tissue injuries of the musculoskeletal system under direct ultrasound visualization. PNE has proven to be effective in tendinosis, 10 plantar fasciitis, 11 whiplash syndrome, 12 and myofascial pain syndrome 13 however, its effectiveness in acute muscle injury is little known. 14,15 Hamstring strains are one of the most common types of acute muscle injuries in nearly all forms of team and individual sports involving the lower body, especially in soccer.…”
Section: Introductionmentioning
confidence: 99%